HUBUNGAN ANTARA SIKAP DAN PERILAKU KOLABORASI DAN PRAKTIK KOLABORASI INTERPROFESIONAL DI RUANG RAWAT INAP RUMAH SAKIT PANTI RAPIH - Lucia Utami; Sunartini Hapsari; Widyandana Widyandana (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2016)
Objective: examines the relationship between physicians–nurses collaboration attitude and behavior and interprofessional collaboration practice in inpatient ward Panti Rapih Hospital, Yogyakarta. Methods: The descriptive study was conducted using a two group design. The estimated available physicians (n=92) and nurses (n=145) were physically in the hospital at the time data collection. Observations carried out on 10 physicians and 10 nurses in inpatient. The instrument used was the Jefferson Scale of Attitudes toward Physician-Nurse Collaboration and The Stickler Collaborative Behavior Scale. Mann Whitney test was used for statistical analysis. Results: The mean score of physician collaborative attitude was 48,24 (SD = 4,671) and nurses was 48,36 (SD = 2,325), p=0,752, there was no statistically significant differences found. While, there were statistical significance differences found between physicians and nurses collaborative behavior (physicians mean score 69,8, SD = 7,88 , nurses 60,31, SD = 9,5, p =0,001). And the correlation between physicians–nurse attitude and behavior toward interprofessional collaboration was significant (p=0,001). Conclusion: both physicians and nurses expressed positive attitudes toward collaboration. Physicians and nurse showed a high level of interacting and interpersonal valuing in a collaborative relationship. There was relationship between physician–nurse collaboration attitude and behavior and interprofessional collaboration practice.